Patient-Reported Outcome Measures as an Intervention: A Comprehensive Overview of Systematic Reviews on the Effects of Feedback - Wittich, Laura; Tsatsaronis, Chrissa; Kuklinski, David; Schöner, Lukas; Steinbeck, Viktoria; Busse, Reinhard; Rombey, Tanja (Value in health, 2024)
Patient-reported outcome measures (PROMs) have emerged as a promising approach to involve patients in their treatment process. Beyond serving as outcome measures, PROMs can be applied to provide feedback to healthcare providers and patients, thereby offering valuable insights that can improve health outcomes and care processes. This overview offers a comprehensive synthesis of the effects of PROM feedback, contributing to the evidence-based discussion on PROMs’ potential to enhance patient care. Following Cochrane Collaboration recommendations, this overview included literature reviews across diverse treatment areas, investigating the impact of PROM feedback on patient health outcomes (including quality of life, symptoms, or survival) and care process outcomes (including communication, symptom identification, or clinical practice). The methodological quality of the evidence was assessed with a modified version of A Measurement Tool to Assess Systematic Reviews 2, and the potential overlap of primary studies was quantified. Results were narratively synthesized. Forty reviews grouped into 4 categories of treatment areas were included. Overall, their methodological quality was low. The overall overlap of primary studies was 2.2%, reaching up to 15.7% within specific treatment areas. The results indicate that PROM feedback may enhance the quality-of-care processes, whereas its effects on patient health outcomes remained less conclusive. PROM feedback positively influences the interaction between physicians and patients across the included treatment areas. Further research is needed to comprehend the trickle-down effects of PROM feedback and how to enhance its potential in yielding health benefits for patients. •Primary studies, reviews, and overviews of Patient-Reported Outcome Measure (PROM) feedback are already present, but their research focus is often limited, primarily concentrating on specific treatment areas or individual outcomes.•This comprehensive overview assesses the influence of PROM feedback on both “patient health outcomes,” such as quality of life, physical or mental symptoms, and “care process outcomes,” such as communication or symptom identification across treatment areas, with no restrictions on single outcome parameters. Additionally, it provides a detailed evaluation of the reviews’ methodological quality.•The results indicate that PROM feedback may enhance care process outcomes, whereas its effects on patient health outcomes remained less definitive. For a comprehensive evaluation of effects on treatment quality, clinical parameters should also be considered. Future research should clearly identify the feedback characteristics so that beneficial elements of the feedback system can be identified and PROM feedback interventions continuously improved.